Sialic acid–binding immunoglobulin-like lectins (Siglecs) detect self-associated molecular patterns to regulate immune responses - Läubli, Heinz (Cell Mol Life Sci, 2019)
The mammalian immune system evolved to tightly regulate the elimination of pathogenic microbes and neoplastic transformed cells while tolerating our own healthy cells. Here, we summarize experimental evidence for the role of Siglecs—in particular CD33-related Siglecs—as self-receptors and their sialoglycan ligands in regulating this balance between recognition of self and non-self. Sialoglycans are found in the glycocalyx and extracellular fluids and matrices of all mammalian cells and can be considered as self-associated molecular patterns (SAMPs). We also provide an overview of the known interactions of Siglec receptors and sialoglycan-SAMPs. Manipulation of the Siglec-SAMP axis offers new therapeutic opportunities for the treatment of inflammatory conditions, autoimmune diseases and also cancer immunotherapy.